Public Satisfaction Index Analysis At The Embong Ijuk Village Office Bermani Ilir District - Putri, Cyndi Dwi; Anggriani, Ida; Putra, Iswidana Utama (Utami Publisher, 2026)
The measurement of the Community Satisfaction Index (IKM) also helps public service implementers identify several aspects that need improvement to enhance the quality of public services, particularly at the Embong Ijuk Village Office, Bermani Ilir District. This study aims to analyze the level of the Community Satisfaction Index (IKM) at the Embong Ijuk Village Office, Bermani Ilir District. The method used refers to the Community Satisfaction Survey (SKM) in accordance with the guidelines stated in the Regulation of the Minister for Administrative and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017, which includes nine indicators: requirements, procedures, completion time, costs/tariffs, product specifications of service types, competence of implementers, behavior of implementers, facilities and infrastructure, as well as complaint handling, suggestions, and feedback. The results of the analysis show that the level of community satisfaction with public services at the Embong Ijuk Village Office achieved an IKM score of 76.75, with a B service quality rating and a “Good” category, as it falls within the conversion value range of 76.61–88.30. The lowest-scoring element was service completion time, with an average of 2.30, categorized as less satisfactory (interval 2.60–3.064). Meanwhile, the highest-scoring element was implementers’ behavior, which obtained an average of 3.29, categorized as Good.